The Roles of Social Support in Promoting Adolescents' Classroom Cognitive Engagement Through Academic Self-Efficacy - Sharifah Azizah Syed Sahil; Rosna Awang-Hashim (Malaysian Journal of Learning and Instruction, 2011)
Purpose – The main aim of the present investigation was to examine the role of teacher, peer, and parental academic and emotional support in predicting adolescent cognitive engagement, especially within the context of ESL classrooms.   Method – The present study examined the availability of academic and emotional support from teachers, classmates and parents as perceived by adolescents, via instruments which were adapted from a number of established measures. This cross-sectional study utilized the survey method, and a total of 450 adolescents from 11 secondary schools in Malaysia, representing early and middle adolescence, took part in the survey. The study assessed each source of support namely teacher, peers and parents within one model.   Findings – Findings from the structural equation modelling suggest that both teacher and parental support are significantly related to adolescent cognitive engagement through their academic efficacy, thus lending support for a full mediation model while peer support was directly related to cognitive engagement.   Significance – Even though parents and teachers played important roles in influencing adolescent cognitive engagement (as suggested by previous studies), this study suggests that the relationship was through academic efficacy, which had served as a mediating variable. One of the contributions of this study is that its findings supported the inclusion of student motivational beliefs in explaining the relationship between support factors and engagement. This study had also examined the unique contribution of emotional support. Additionally, it was found that research should not disregard the importance of peers in promoting cognitive engagement directly.